PENGARUH KOMPENSASI, GAYA KEPEMIMPINAN, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (Studi kasus pada PT. Ago Furindo Semarang) - Michael Surya Pranata, 13.05.51.0179 (Students Journal of Economic and Management, 2017)
The purpose of this study is to determine the effect of compensation, leadership style, organization culture toward the employee performance. The sampling of this research was using saturate sampling technique over 70 respondents. Collecting data was using questionnaire by distributing to the respondents to collect the information. Using Correlation to find the validity of data, using Cronbach alpha to find the reliability of data, also using regression analysis to find the score of variable effect. Furthermore, the results of the research are: (1) Compensation has positive and significant impact toward the employee performance. (2) Leadership style has positive and significant impact toward the employee performance. (3) Organization culture has positive and significant impact toward the employee performance.Â Keywords: Compensation, Leadership Style, Organization Culture